The effect of a physical activity intervention on preschoolers' fundamental motor skills — A cluster RCT. Issue 7 (July 2018) - Wasenius, Niko S.; Grattan, Kimberly P.; Harvey, Alysha L.J.; Naylor, Patti-Jean; Goldfield, Gary S.; Adamo, Kristi B.
Abstract: Objectives: To assess the effect of a physical activity intervention delivered in the childcare centres (CC), with or without a parent-driven home physical activity component, on children's fundamental motor skills (FMS). Design: Six-month 3-arm cluster randomized controlled trial. Methods: Preschoolers were recruited from 18 licensed CC. CC were randomly assigned to a typical curriculum comparison group (COM), childcare intervention alone (CC), or childcare intervention with parental component (CC + HOME). FMS was measured with the Test of Gross Motor Development-2. Linear mixed models were performed at the level of the individual while accounting for clustering. Results: Raw locomotor skills score increased significantly in the CC group (mean difference = 2.5 units, 95% Confidence Intervals, CI, 1.0–4.1, p < 0.001) and the CC + HOME group (mean difference = 2.4 units, 95% CI, 0.8–4.0, p < 0.001) compared to the COM group. No significant (p > 0.05) between group differences were observed in the raw object control skills, sum of raw scores, or gross motor quotient. No significant sex differences were found in any of the measured outcomes. Conclusions: A physical activity intervention delivered in childcare with or without parents' involvement was effective in increasing locomotor skills in preschoolers.